The Implication of Teachers’ Politeness Strategy In Teaching on Higher Institution - Dian Anggraini; Ryan Hidayat Rafiola; Vivi Nila Sari; Desi Andriani (Fakultas Sastra Universitas Ekasakti, 2022)
This research aims to explain the types of politeness strategies used by teachers and students in class interactions, how these strategies are manifested in actions in class interactions and pedagogical functions of politeness strategies. The subjects in this study are teachers and students who used politeness strategies as many as 52 students and one teacher in the learning and teaching process. The research is a qualitative research. Data collected through observation and interviews. The results showed that is used by students to talk to the teacher when the meaning of speech is conveyed implicitly. There are four pedagogic functions in politeness strategies, namely giving the distance between teacher and students, atmosphere in class, reducing student tension, and making social interaction between teacher and students.